Editorial: Landscape evolution of the tropical regions: Dates, rates and beyond - Pupim, Fabiano do Nascimento (2022)
The Tropics represent a large portion of Earth’s continents, including the highest mountains, ancient flat surfaces, arid landscapes, major rivers, floodplains, and deltas. These contrasting landscapes play critical roles in land-sea sediment fluxes, biogeochemical cycles, global climate change, critical zone processes, biodiversity conservation, and supporting densely populated urban centers. Studying these landscapes since the 19th century, geoscientists have gained a greater understanding of how they were formed and evolved through time. However, a recent boom in new methods and techniques has allowed the quantification of the timing and rates of the processes that shape these landscapes and has driven a transformative revolution in understanding tropical surface dynamics. In this Research Topic, we bring together the contributions of scientists from across disciplines who share a common interest in applying quantitative approaches to investigate the internal and surface processes that drive landscape evolution in the Tropics. It gathers six original articles covering unresolved questions about the timing and rates of tropical weathering and river and wetlands evolution.The Tropics represent a large portion of Earth’s continents, including the highest mountains, ancient flat surfaces, arid landscapes, major rivers, floodplains, and deltas. These contrasting landscapes play critical roles in land-sea sediment fluxes, biogeochemical cycles, global climate change, critical zone processes, biodiversity conservation, and supporting densely populated urban centers. Studying these landscapes since the 19th century, geoscientists have gained a greater understanding of how they were formed and evolved through time. However, a recent boom in new methods and techniques has allowed the quantification of the timing and rates of the processes that shape these landscapes and has driven a transformative revolution in understanding tropical surface dynamics. In this Research Topic, we bring together the contributions of scientists from across disciplines who share a common interest in applying quantitative approaches to investigate the internal and surface processes that drive landscape evolution in the Tropics. It gathers six original articles covering unresolved questions about the timing and rates of tropical weathering and river and wetlands evolution.